Android Application for Determining Growth and Development of Children Aged 0-5 Years using The Denver II Test - Purnamasari, Feby; Selvia, Selvia (jitek, 2023)
Health services in the form of information technology are needed to advance health services. Applications for child development are very necessary during the pandemic because of the limitations of direct visits by health workers to residents' homes, so an android application is needed as a screening method to determine child growth and development so that it can detect developmental delays in children from an early age. This study uses the Denver II test to design an android application to determine the growth and development of children aged 0-5 years. The design of the application system starts with observations and interviews, after which the process of designing and making an offline-based android application programming system is carried out. This application has been tested pretest and posttest on 30 mothers who have children aged 0-5 years. The Wilcoxon test carried out these results with a 0.000 <0.005, so there is a difference between the pretest and posttest knowledge results. The conclusion is that parents can use this application to monitor the growth and development of children aged 0-5 years